Utility and safety of balloon-assisted enteroscopy in patients with left ventricular assist devices: a retrospective multicenter study - Hasan, Badar M.; McMahon, Charles; Khalid, Rumman A.; Colak, Yasar; Mayorga, Daniel C.; Elkafrawy, Ahmed; Tandon, Kanwarpreet; Shafiq, Muhammad; Hussain, Ishtiaq; Erim, Tolga; Castro, Fernando; Charles, Roger; Chhabra, Rajiv (Endoscopy International Open, 2020)
Objective and study aims Patients with left-ventricular assist devices (LVADs) have an increased risk of gastrointestinal bleeding, especially from the small bowel, often necessitating evaluation with balloon-assisted enteroscopy (BAE). Our study aimed to assess the periprocedural safety and utility of BAE for gastrointestinal bleeding in patients with LVADs.Patients and methods This was a multicenter retrospective cohort study of adults with LVADs who underwent BAE between January 2007 to December 2018.Results Thirty-four patients underwent a total of 46 BAEs (9 were single-balloon enteroscopies [SBEs] and 37 were double-balloon enteroscopies [DBEs]). Mean age of patients was 66.4 ± 8.3 years. Patients tolerated anesthesia well, without complications. There were no complications from the BAE itself. One patient required repeat BAE due to a progressive drop in hemoglobin and another patient developed paroxysmal supraventricular tachycardia. One patient died within 72 hours of the procedure due to worsening of LVAD thrombosis. Diagnostic yields were 69.6 % for all procedures, 73.0 % for DBE and 55.6 % for SBE (P = 0.309). Therapeutic yields were 67.4 % overall: 73.0 % for DBE and 44.4 % for SBE (P = 0.102). In those that presented with overt gastrointestinal bleeding, DBE had a higher diagnostic yield compared to SBE (84.2 % vs. 42.9 %; P = 0.057) and a significantly higher therapeutic yield (84.2 % vs. 28.6 %; p = 0.014).Conclusions This is the largest multicenter study of patients with LVADs who underwent DBE. BAE appears to be a safe and useful modality for the evaluation of gastrointestinal bleeding in these patients.